Islamic Philanthropy in the Digital Era: The Role of Media and Culture in Spreading the Teachings of Generosity - Muhammad Mansur; Addiarrahman Addiarrahman; Dailani Ismail; Abdullah Rasyidi; Muhammad Deni Putra (MD Research Center, 2025)
This study aims to examine the strengthening of the Islamic philanthropy ecosystem through collaboration between media, Islamic institutions, and society, with a focus on the role of media in reinforcing Islamic philanthropic values in the digital age. In this context, both traditional and digital media are identified as highly influential forces in expanding reach and encouraging public participation in philanthropic activities. However, this study also highlights the primary challenge of misrepresenting the principles of Islamic philanthropy in mainstream media, which often obscures the public’s understanding of the broader characteristics and goals of charity in Islam beyond just financial donations. The study employs a qualitative approach using a literature review method, analyzing various related literature such as scholarly articles, research reports, and books on Islamic philanthropy, media, and community involvement. This research also explores the potential of social media as a tool to broaden the reach of philanthropy, particularly among the youth, as well as the importance of transparency and accountability in digital-based philanthropic campaigns. The findings of this research suggest that effective collaboration between media, Islamic institutions, and society can create a greater social impact, raise awareness about the importance of philanthropy, and increase participation in charitable activities. However, to achieve these goals, the use of media must be done wisely and ethically, with a focus on creating authentic narratives and managing transparency. This study provides new insights into how such collaboration can strengthen the Islamic philanthropy ecosystem in the modern era.